Impact of high‐risk glycemic control on habitual sleep patterns and sleep quality among youth (13–20 years) with type 1 diabetes mellitus compared to controls without diabetes - Rose, Shelley; Boucher, Sara E.; Galland, Barbara C.; Wiltshire, Esko J.; Stanley, James; Smith, Claire; Bock, Martin I.; Rayns, Jenny A.; MacKenzie, Karen E.; Wheeler, Benjamin J. (Pediatric diabetes, 2021)
Background In type 1 diabetes mellitus (T1D), glycemic control and sleep have a bidirectional relationship, with unhealthy glycemic control impacting sleep, and inadequate sleep impacting diabetes management. Youth are at risk for poor quality sleep; however, little is known about sleep among youth with high‐risk glycemic control. Objective To assess differences in habitual sleep timing, duration, and quality among youth with T1D and controls. Subjects Two‐hundred‐thirty youth (13–20 years): 64 with T1D (mean age 16.6 ± 2.1 years, 48% female, diabetes duration 7.5 ± 3.8 years, HbA1c 96 ± 18.0 mmol/mol [10.9 ± 1.7%]), and 166 controls (mean age 15.3 ± 1.5, 58% female). Methods Comparison of data from two concurrent studies (from the same community) using subjective and objective methods to assess sleep in youth: Pittsburgh Sleep Quality Index evaluating sleep timing and quality; 7‐day actigraphy measuring habitual sleep patterns. Regression analyses were used to compare groups. Results When adjusted for various confounding factors, youth with T1D reported later bedtimes (+36 min; p < 0.05) and shorter sleep duration (−53 min; p < 0.05) than controls, and were more likely to rate subjective sleep duration (OR 3.57; 95% CI 1.41–9.01), efficiency (OR 4.03; 95% CI 1.43–11.40), and quality (OR 2.59; 95% CI 1.16–5.76) as “poor” (p < 0.05). However, objectively measured sleep patterns were similar between the two groups. Conclusions Youth with high‐risk T1D experience sleep difficulties, with later bedtimes contributing to sleep deficit. Despite a lack of objective differences, they perceive their sleep quality to be worse than peers without diabetes.